Agricultural Landscape Preferences: Implications for Agritourism Development. (May 2014) - Gao, Jie; Barbieri, Carla; Valdivia, Corinne
This study examines residents' preferences for agricultural landscape features when engaging in agritourism activities by addressing two objectives: (1) to identify the features of agricultural landscapes that are more appealing to current and potential agritourists and (2) to compare those perceptions across respondents from different genders, agritourism experience, and agricultural attachment. Data were collected through an online survey conducted among three nonrandom panels of residents from Missouri, Pennsylvania, and Texas (250 per state). Results showed that respondents liked most landscape features commonly found in an agritourism farm, especially natural and cultural ones. Among these, the most preferred features they would like to see are wildlife, water resources, historic elements, and farm animals, suggesting that these can serve as farm pull attractions. Multivariate analyses of variance showed significant differences in landscape preferences across gender, levels of agritourism experience, and agricultural attachment, suggesting critical marketing and managing implications for farmers offering agritourism opportunities.